Prevalence of Postural Biomechanical Awareness among Male and Female Paramedical Staff During Patient Transfer-A Comparative Study - Ayesha Sadiq, Misbah Waris, Maryem Manzoor Ahmed, Irum Riaz, Shahtaj Fatima, Hafiza Aamna, Sadaf Waris, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This comparative study was conducted to investigate the knowledge and practice of correct postural biomechanical awareness among male and female paramedical staff during patient transfer. Methods: Data was collected from Surgical, Orthopedic, Emergency, Operation Theater, Gynae & Labor wards of 20 different hospitals and institutes of Lahore i.e. Services Hospital, Jinnah Hospital, UOL Teaching Hospital, Gulab Devi Hospital, Mayo Hospital, Bajwah Hospital, Iqra Medical Complex, Gosha e Shifa Hospital, Farooq Hospital, Fatima Memorial Hospital, Hajrah Hospital, Ganga Ram Hospital, Life Care Hospital, General Hospital, Hameed Latif, Wapda Hospital, Najam Hospital, PSRD Hospital, Children Hospital, Rescue 1122 (EMS=Emergency Medical Services). Data was collected from these paramedics including Ward boys, Nurses, Midwives and EMS. A comparative cross-sectional survey was conducted and 210 members were studied. A well-structured questionnaire(1) based on Thurston scale “yes” and “no” was used, which was filled by both gender paramedics working in these settings. All participants were chosen via simple random sampling. Results: Results were divided in three domains. First assessed demographics, second assessed knowledge while Third domain assessed the practice of knowledge by the participants. Results were represented in Graphs, Tables and Cross Tabulations. Data was analyzed on SPSS (version 20). First domain showed that participants are usually from lower class and least from middle class, second domain determines that female participants have good knowledge in contrast to third domain that showed that male participants have good practice. Conclusion: Valid Conclusion showed that both gender participants should increase both knowledge as well as practice of Correct postural biomechanics.